1984
DOI: 10.1002/j.1460-2075.1984.tb01785.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of a new mitochondrially synthesized proteolipid of the ATP synthase of Saccharomyces cerevisiae.

Abstract: The purification and the amino acid sequence of a proteolipid translated on ribosomes in yeast mitochondria is reported. This protein, which is a subunit of the A TP synthase, was purified by extraction with chloroform/methanol (2/1) and subsequent chromatography on phosphocellulose and reverse phase h.p.l.c. A mol. wt. of 5500 was estimated by chromatography on Bio-Gel P-30 in 8011/o fonnie acid. The complete amino acid sequence of this protein was determined by automated solid phase Edman degradation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 42 publications
(42 reference statements)
4
25
0
Order By: Relevance
“…In contrast, Y8, both as the authentic in vivo product (lane 1) or the in vitro translation product of the NAP8 gene (lane 3), shows mobility consistent with its actual size of 5.8 kDa [12, 131 also paralleling the size estimated by gel permeation chromatography [25]. One should note in passing that the anomalous mobility of yeast subunit 9 has led to subunit 8 being incorrectly referred to as a 10-kDa protein [25 -281, merely because the more rapidly moving subunit 9 was erroneously taken as a reliable 8-kDa size/mobility standard.…”
Section: Synthesis Of Nap9mentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast, Y8, both as the authentic in vivo product (lane 1) or the in vitro translation product of the NAP8 gene (lane 3), shows mobility consistent with its actual size of 5.8 kDa [12, 131 also paralleling the size estimated by gel permeation chromatography [25]. One should note in passing that the anomalous mobility of yeast subunit 9 has led to subunit 8 being incorrectly referred to as a 10-kDa protein [25 -281, merely because the more rapidly moving subunit 9 was erroneously taken as a reliable 8-kDa size/mobility standard.…”
Section: Synthesis Of Nap9mentioning
confidence: 85%
“…On account of their solubility in chloroform/ methanol [20], both subunit 9 [2] and subunit 8 [25] are termed proteolipids. Fig.…”
Section: Synthesis Of Nap9mentioning
confidence: 99%
“…Thus it has been shown that both transmembrane stems (4) and a hydrophilic charged loop (5) of subunit 9 (76 amino acids), together with two of the five or more transmembrane stems (6) of subunit 6 (259 amino acids), participate in protonophoric functions and energy coupling (3). Studies on protein assembly (7) have shown that subunit 8, a 48-amino acid polypeptide (8) with a single transmembrane stem (9), is required for the assembly of subunit 6 into the mtATPase complex, while the assembly of subunit 8 is dependent upon the correct integration of subunit 9 into the membrane (2).…”
mentioning
confidence: 99%
“…These proteins may be called proteolipids which are extracted from the samples by using organic solvents such as a mixture of chloroform and methanol (Velours et al, 1984). An aqueous solution containing mild detergents such as Triton X-100 and CHAPS is an alternative way to dissolve the proteins from cells or organelles.…”
Section: Extraction Of Lipid-soluble Proteinmentioning
confidence: 99%